2020
DOI: 10.3390/atmos11090967
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Urban Greening in a District of Lecce (Southern Italy) for the Analysis of CO2 Storage and Air Pollutant Dispersion

Abstract: This paper is devoted to the assessment of urban greening effects on two important ecosystem services, i.e., air quality and CO2 storage, including the corresponding economic impacts in a real urban area, i.e., a district located in the Mediterranean city of Lecce (southern Italy). Two tools were employed, i-Tree Canopy and the computational fluid dynamics (CFD) microclimate model ENVI-met. i-Tree Canopy allowed fully determining the land-cover percentage on the basis of different ground cover classes and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 76 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…These evolutionary scenarios will measure thermo-regulatory actions related to energy efficiency or greening strategies (e.g., desealing, micro-forestation, rain gardens, green roofs, cool and high albedo/reflectance materials, etc.) as tested on various scales in several GIScience or ENVI−met studies [5,[44][45][46][47]. On the other hand, they will be completed with aestheticperceptive and socio-recreational analyses through an integrated, technological-traditional approach as developed in CCUHRE project.…”
Section: Discussionmentioning
confidence: 99%
“…These evolutionary scenarios will measure thermo-regulatory actions related to energy efficiency or greening strategies (e.g., desealing, micro-forestation, rain gardens, green roofs, cool and high albedo/reflectance materials, etc.) as tested on various scales in several GIScience or ENVI−met studies [5,[44][45][46][47]. On the other hand, they will be completed with aestheticperceptive and socio-recreational analyses through an integrated, technological-traditional approach as developed in CCUHRE project.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that, on a typical summer day, the greening has a positive effect on thermal comfort by decreasing PMV of 2 points and MRT by 7 • C and that these variations are also related to urban morphology and greening type. Buccolieri et al [21] investigated the effect of greening in the "Santa Rosa" neighbourhood (also studied here) on the dispersion of nitrogen oxides (NOx) and on CO 2 storage. A further neighbourhood, "167", is under investigation and will be the subject of a future publication.…”
Section: Study Area: An Overview On Lecce Citymentioning
confidence: 99%
“…Regarding the Santa Rosa neighbourhood, Buccolieri et al [21] reported part of the experimental campaign, which is summarised here and compared with the Libertini one.…”
Section: Description Of the Neighbourhoodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the assessment of greening effects in urban areas is a complex task [6], as detailed in the study of the Santa Rosa district in the Mediterranean city of Lecce, located in Southern Italy. Lecce is a medium-sized city of 96,534 inhabitants, representative of Mediterranean cities in terms of architectural design and climate.…”
mentioning
confidence: 99%